2008
DOI: 10.1073/pnas.0803195105
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic glycopeptide vaccines combining β-mannan and peptide epitopes induce protection against candidiasis

Abstract: The first fully synthetic glycopeptide vaccines against a fungal disease have been used to combat disseminated candidiasis in mice. Six T cell peptides found in Candida albicans cell wall proteins were selected by algorithm peptide epitope searches; each was synthesized and conjugated to the fungal cell wall ␤-mannan trisaccharide [␤-(Man) 3] by novel saccharide-peptide linker chemistry to create glycopeptide conjugates. The six proteins were selected because of expression during human candidiasis and cell wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
215
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 206 publications
(228 citation statements)
references
References 43 publications
10
215
0
1
Order By: Relevance
“…Disappointingly, the same vaccine given to mice produced corresponding titers of 10,000 or lower, and these Ab levels were not significantly improved by more aggressive immunization protocols that employed powerful adjuvants such as CFA (33). However, when an Ag-pulsed DC-based vaccine strategy was used, b-mannan trisaccharide-peptide conjugates were able to protect mice in a disseminated candidiasis model of disease (10). This result prompted us to consider targeting the trisaccharidetetanus toxoid (TS-TT) conjugate vaccine to DCs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Disappointingly, the same vaccine given to mice produced corresponding titers of 10,000 or lower, and these Ab levels were not significantly improved by more aggressive immunization protocols that employed powerful adjuvants such as CFA (33). However, when an Ag-pulsed DC-based vaccine strategy was used, b-mannan trisaccharide-peptide conjugates were able to protect mice in a disseminated candidiasis model of disease (10). This result prompted us to consider targeting the trisaccharidetetanus toxoid (TS-TT) conjugate vaccine to DCs.…”
mentioning
confidence: 99%
“…The poor outcome of almost half the patients treated with appropriate antifungal therapy has spurred the development of preventative measures such as active immunization strategies (3)(4)(5). Although a few existing candidate vaccines show promise (6)(7)(8)(9), others require aggressive immunization protocols and remain less satisfactory (10). We envisaged a conjugate vaccine based on the protective b-mannan epitope of Candida albicans conjugated to tetanus toxoid (11), a licensed carrier protein, with a third component, a b-glucan, that engages Dectin-1, a C-type lectin receptor of the dendritic cell (DC) and targets the vaccine to these professional APCs.…”
mentioning
confidence: 99%
“…Cutler and co-workers (9 -11) have shown that glycoconjugates prepared from native antigen as well as monoclonal antibodies specific for this antigen afford protection in active and passive immunization protocols. Results from our laboratory from immunizations with synthetic di-and trimannoside tetanus toxoid (12) or albumin 2 conjugates showed protection in a rabbit model of candidiasis, and work with Cutler and co-workers (13) has demonstrated the promise of trimannoside-peptide conjugates in the design of a Candida vaccine.…”
mentioning
confidence: 99%
“…Ces moyens reposent sur les antifongiques (dont l'efficacité a été prouvée au niveau systémique, mais jamais intestinal), les souches probiotiques de S. cerevisiae dont il est intéressant de noter, à l'inverse, que leur effet a été rapporté à la fois sur la colonisation par C. albicans, sa dissémination et sur l'inflammation. À plus long terme on peut évoquer les vaccins anti-C. albicans dont deux au moins ciblent les glycannes que nous avons décrits [37,49] et arrivent à un stade de développement qui justifiera d'ici peu des études cliniques, tout au moins pour lutter contre les candidoses invasives. Enfin, les résultats négatifs de toutes les études menées à ce jour à la recherche d'autres immunogènes microbiens ou auto-(néo) antigènes à l'origine des anticorps antiglycannes au cours de la MC n'excluent pas leur existence.…”
Section: Synthèse Et Perspectives Fondamentales Et Cliniques Concernaunclassified